The Agricultural Supply Chain Systems in Cooperation and Integration of Agro-Industrial Complexes of Russia - Kalykova, Bakyt; Kaiyrbayeva, Ainur; Nurmanbekova, Gulmira; Yeltayeva, Kuralay; Rakhimzhanova, Gaukhar (International Journal of Supply Chain Management, 2018)
Abstract- This article is devoted to cooperation and integration development as agricultural supply chain systems in the Agro-Industrial Complexes (AICs) of Russia and Kazakhstan. This article reveals the correlation between investments and the number of coops (0.8), between the state backing and the number of coops in Russia (0.87), Kazakhstan (0.9), and the USA (0.76).  Article content demonstrates that the Pearson coefficient of correlation between the number of coops and the specific weight of produced wheat is below the average standard in Kazakhstan (0.4), as the integration & cooperation policy is only starts to take a shape.